Viability, Germination and Mycoflora of Pongamia pinnata as Influenced by Seeds Stored in Different Storage Containers - Handa, A.K.; ., Ajit; Singh, Kundan; Kumar, R.V.; ., Uma; Chauhan, Ruchi; Meena, Anjana (Indian Journal of Agroforestry, 2020)
Under the present investigation, fresh seeds of Pongamia pinnata were collected from Jhansi, Lalitpur, Jabalpur and Nagpur during January to end of February and stored at room temperature (Â± 26Â°C average) using different containers i.e., paper bag, gunny bag, plastic bag and airtight plastic container for a period of 2 years. Seed viability was found 100 % at the time of seed collection, however, after one year of storage period, seed viability and germination was observed maximum in airtight plastic containers. The seed viability and germination was deprived in paper bag container, however no adverse effect was observed on the growth of seedlings raised from the seeds stored in it and was at par with other containers and recorded more values for height, collar diameter and root/shoot biomass. Twenty-three fungi belong to 17 genera were isolated from the seeds of Pongamia pinnata stored in different types of containers after two years. Maximum fungi were reported in gunny bags, followed by paper bags, polythene bags and airtight polythene bag’s stored seeds. On the basis of above findings, it is inferred that seed viability and germination decreased with increase in storage period.